Molecular Characterization of AMPA-Receptor-Containing Vesicles - Peters, John Jacob; Leitz, Jeremy; Oses-Prieto, Juan A.; Burlingame, Alma L.; Brunger, Axel T. (Frontiers in Molecular Neuroscience, 2021)
Regulated delivery of AMPA receptors (AMPARs) to the postsynaptic membrane is an essential step in synaptic strength modification, and in particular, long-term potentiation (LTP). While LTP has been extensively studied using electrophysiology and light microscopy, several questions regarding the molecular mechanisms of AMPAR delivery via trafficking vesicles remain outstanding, including the gross molecular make up of AMPAR trafficking organelles and identification and location of calcium sensors required for SNARE complex-dependent membrane fusion of such trafficking vesicles with the plasma membrane. Here, we isolated AMPAR containing vesicles (ACVs) from whole mouse brains via immunoisolation and characterized them using immunoelectron microscopy, immunoblotting, and liquid chromatography tandem mass spectrometry (LC-MS/MS). We identified several proteins on ACVs that were previously found to play a role in AMPAR trafficking, including synaptobrevin-2, Rabs, the SM protein Munc18-1, the calcium-sensor synaptotagmin-1, as well as several new candidates, including synaptophysin and synaptogyrin on ACV membranes. Additionally, we identified two populations of ACVs based on size and molecular composition: small-diameter, synaptobrevin-2- and GluA1-containing ACVs and larger transferrin-receptor-, GluA1-, GluA2-, GluA3-containing ACVs. The small-diameter population of ACVs may represent a fusion-capable population of vesicles due to the presence of synaptobrevin-2. Because the fusion of ACVs may be a requisite of LTP, this population could represent trafficking vesicles related to LTP.